2020
DOI: 10.1186/s40644-020-0289-2
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion and ADC measurements for differentiating benign from malignant thyroid nodules: utilizing the most repeatable region of interest delineation at 3.0 T

Abstract: Background: There is a growing need for a reproducible and effective imaging method for the quantitative differentiation of benign from malignant thyroid nodules. This study aimed to investigate the performances of intravoxel incoherent motion (IVIM) parameters and the apparent diffusion coefficient (ADC) in differentiating malignant from benign thyroid nodules derived from the most repeatable region of interest (ROI) delineation. Methods: Forty-three patients with 46 pathologically confirmed thyroid nodules u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…IVIM-DWI is a non-invasive technique that shows superiority in reflecting tumor cellularity and perfusion without requiring a contrast agent. It has already been applied in the differentiation of lung nodules ( 29 ), thyroid nodules ( 30 ), and breast ( 31 ) and brain tumors ( 32 ) with good diagnostic performance. To our best knowledge, no prostate study with a large sample size has been reported to determine the value of IVIM to quantitatively distinguish PCa from non-cancerous tissues and identify the tumor Gleason grades, in the background of IVIM becoming a research hotspot in whole-body tumors.…”
Section: Discussionmentioning
confidence: 99%
“…IVIM-DWI is a non-invasive technique that shows superiority in reflecting tumor cellularity and perfusion without requiring a contrast agent. It has already been applied in the differentiation of lung nodules ( 29 ), thyroid nodules ( 30 ), and breast ( 31 ) and brain tumors ( 32 ) with good diagnostic performance. To our best knowledge, no prostate study with a large sample size has been reported to determine the value of IVIM to quantitatively distinguish PCa from non-cancerous tissues and identify the tumor Gleason grades, in the background of IVIM becoming a research hotspot in whole-body tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-needle aspiration is an invasive examination, and one-third of the results are inconclusive (3). With the rapid development of magnetic resonance imaging, some functional sequences have achieved better diagnostic performance, but this method has the disadvantages of being high cost and time-consuming (6). Computed tomography (CT) can be used to identify nodules, establish preoperative localization, provide information for the diagnosis, and assess the therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%
“…IVIM-DWI is a noninvasive technique that shows superiority in reflecting tumor cellularity and perfusion without the need of contrast agent. It had already been applied in the differentiation of thyroid nodules [ 22 ], breast [ 23 ], liver [ 24 ] and brain tumors [ 25 ] with good diagnostic performance. To our best knowledge, there is still no pulmonary study with large sample size to settle down the value of IVIM for quantitatively distinguishing lung cancer from benign tissues, in the background of IVIM becoming a research hotspot in the whole-body tumors.…”
Section: Discussionmentioning
confidence: 99%